Hipertensão arterial e cuidados com a saúde: concepções de homens e mulheres - Frascá, Mariana Girotto da Silva [UNESP] (2014)
The arterial hypertension is an illness linked to lifestyle, reasons of ambiental and behavioral patterns. Show chronic and asymptomatic process, with multiple factors of complex risk having your control necessary to prevention or reduction on incidence of complications and to improve the quality of life. The goal of this research was to analyze accounts of men and woman suffering from high blood pressure on behaviors, beliefs and feelings about illness and health care, besiders correlate beliefs and feelings with behaviors relating the health and illness. Had participate this research 40 carrier disease of arterial hypertension, 20 men and 20 women, patients of private health service destined to prevention and control of ills. All participants were inserting in a group of health education. The way used was structured interviews, with opened and closed questions that include aspects about arterial hypertension. The reviews were made by analysis of content and statistical tests. The results showed how was established the history of hypertension and what was the definition about hypertension by participants, were described the process of causality and prevention, the behaviors displayed after diagnosed, the feelings related to illness and connection with the service and professionals of health system. Behavior of procrastination, feelings of guilt, afraid and difficulty with changes of habits were studied too. In a general, the character asymptomatic and unpredicatable of hypertension was highlighted. Was note that participants had knowledge about factors of risk to increase of pressure and the behaviors required to control showing that action of prevention was focused in practice of life. The emotional factors were said many times, mainly to blame it for aggravation and contextualize it. The feelings identified had indicated the possibility of live peacefully with illness to some participants and worries with diagnosed to others, especially...